Transfer mode effects on Ti6Al4V wall building in wire laser additive manufacturing. (April 2021) - Mortello, M.; Casalino, G.
Highlights: Monitoring metal transfer dynamics helps to understand the variables setting. Surface tension transfer mode produces smooth and regular deposition. The transfer mode can enhance geometrical wall and metal microstructure. Abstract: This paper analyses the metal transfer process dynamics to assess how weld pool, laser source and filler wire interact to establish a stable and smooth deposition. The investigation led to the definition of suitable manufacturing settings and process parameters. Satisfactory geometrical and microstructural properties were achieved for a 15-layer titanium alloy wall.